New species and global revision of Hippasteria (Hippasterinae: Goniasteridae; Asteroidea; Echinodermata). (June 2014) - Mah, Christopher; Neill, Kate; Eléaume, Marc; Foltz, David
<x xml:space="preserve">Abstract</x> A molecular phylogenetic analysis of the genus Hippasteria, rooted against Evoplosoma, has provided the basis for taxonomic revisions and provided insight into the biogeography of a widely occurring, cold‐water group of corallivorous asteroids. Herein, we describe three new species, Hippasteria mcknighti sp. nov., Hippasteria muscipula sp. nov., and Hippasteria tiburoni sp. nov., from deep‐water settings. Additionally, in light of taxonomic changes, we further elaborate on distribution data for multiple species. Range extensions for Hippasteria phrygiana and Hippasteria californica are included. Discussions about biogeography, cladogenic events, and morphology are also presented. © 2014 The Linnean Society of London